“COAGULATION”: a mnemonic device for treating coagulation disorders following traumatic brain injury—a narrative-based method in the intensive care unit - Quintana-Diaz, Manuel; Anania, Pasquale; Juárez-Vela, Raúl; Echaniz-Serrano, Emmanuel; Tejada-Garrido, Clara Isabel; Sanchez-Conde, Pilar; Nanwani-Nanwani, Kapil; Serrano-Lázaro, Ainhoa; Marcos-Neira, Pilar; Gero-Escapa, María; García-Criado, Jorge; Godoy, Daniel Agustín (Frontiers in Public Health, 2023)
Introduction Coagulopathy associated with isolated traumatic brain injury (C-iTBI) is a frequent complication associated with poor outcomes, primarily due to its role in the development or progression of haemorrhagic brain lesions. The independent risk factors for its onset are age, severity of traumatic brain injury (TBI), volume of fluids administered during resuscitation, and pre-injury use of antithrombotic drugs. Although the pathophysiology of C-iTBI has not been fully elucidated, two distinct stages have been identified: an initial hypocoagulable phase that begins within the first 24 hours, dominated by platelet dysfunction and hyperfibrinolysis, followed by a hypercoagulable state that generally starts 72 hours after the trauma. The aim of this study was to design an acronym as a mnemonic device to provide clinicians with an auxiliary tool in the treatment of this complication. Methods A narrative analysis was performed in which intensive care physicians were asked to list the key factors related to C-iTBI. The initial sample was comprised of 33 respondents. Respondents who were not physicians, not currently working in or with experience in coagulopathy were excluded. Interviews were conducted for a month until the sample was saturated. Each participant was asked a single question: Can you identify a factor associated with coagulopathy in patients with TBI? Factors identified by respondents were then submitted to a quality check based on published studies and proven evidence. Because all the factors identified had strong support in the literature, none was eliminated. An acronym was then developed to create the mnemonic device. Results and Conclusion Eleven factors were identified: Cerebral Computed Tomography, Oral Anticoagulant & Antiplatelet Use, Arterial Blood Pressure (Hypotension), Goal-Directed Haemostatic Therapy, Use Fluids Cautiously, Low Calcium Levels, Anaemia-Transfusion, Temperature, International Normalised Ratio (INR), Oral Antithrombotic Reversal, Normal Acid-Base Status, forming the acronym “Coagulation”. This acronym is a simple mnemonic device, easy to apply for anyone facing the challenge of treating patients of moderate or severe TBI on a daily basis.